THE DEFINITION OF POLITICAL OPPOSITION IN THE CONTEXT OF SPECIFICITY OF UKRAINIAN POLITICS - Манойло, Д.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Approaches to the definition of the political opposition, which today are used in ukrainian and foreign political science, are reviewed and analyzed in detail in the article. Specific features of Ukrainian politics, which should be taken into account in determining the political opposition, are studied. During the study, concepts such as the „opposition”, „parliamentary opposition" and „political opposition" were branched. Approach that is most appropriate to the determination of the political opposition in the context of Ukrainian policy is proposed.